The combined effect of acetone and ZnO with diesel-biodiesel blends on the performance, combustion and emission characteristics of diesel engine - Dhanarasu, M (Environmental technology, 2023)
In this experimental study, the performance, combustion and emission analysis of the combined effect of acetone and Zinc Oxide (ZnO) dispersed diesel-biodiesel (B20) blends were done in four-stroke, single-cylinder and water-cooled diesel engine. ZnO was synthesized by the solvothermal method using cow urine as a solvent and reducing agent. The synthesized ZnO was characterized by X-ray diffraction (XRD) and Scanning Electron Microscope (SEM). The biodiesel was produced from waste cooking oil through a trans-esterification process. The synthesized ZnO was dispersed in 10, 20 and 30 ppm with diesel-biodiesel blend along with 10% of acetone to form B20A10Zn10, B20A10Zn20 and B20A10Zn30 test fuels. The experimental results show that adding acetone and ZnO with diesel-biodiesel blend tends to promising physiochemical properties of the test fuels and produced better results in performance and emission. The test fuel, B20A10Zn30, gave a better outcome than all other fuels and recorded a 0.4% increase in Brake Thermal Efficiency (BTE), while there was an 8% increase in Brake Specific Fuel Consumption (BSFC). Compared to diesel, the emissions, such as Carbon Monoxide (CO), Unburned Hydrocarbon (UHC), Oxides of Nitrogen (NOx), and smoke, were 7.97%, 20%, 1.8% and 1.49% lower than the conventional diesel